Apakah Hedonic Shopping Motivation, Sales Promotion & Digital Payment Dapat Mendorong Keputusan Impulsive Buying?: Survei Pada Konsumen Generasi Z Wilayah Kecamatan Bergas yang Berbelanja di Shopee - Putri, Puput Novelia; Nurmiyati; Supraptini, Nunuk (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The rapid development of e-commerce and the ease of digital payment transactions have led to significant changes in consumer shopping patterns, especially among Generation Z. One phenomenon that has emerged is impulsive buying, where consumers purchase items without prior planning. This study investigates the influence of hedonistic shopping motivation, sales promotion, and digital payment methods on impulse purchases of Shopee customers in Bergas district. The research method used is quantitative and based on purposive sampling. The sample includes 110 customers who have shopped at Shopee more than twice. The analysis shows that all three independent variables have a significant influence on impulse purchases. Sales promotion has the largest influence of 33.3%. This shows that sales promotions such as discounts and attractive offers greatly encourage customers to make impulse purchases. Digital payments contribute 24.2%. This shows that the ease of digital transactions makes it easier for customers to make purchases without much thought. Meanwhile, Hedonic Shopping Motivation contributes 20.8%, indicating that the pleasure and emotional satisfaction consumers gain during shopping also influence their decision to buy impulsively. This study concludes that the combination of attractive sales promotions, ease of digital payments, and hedonic shopping motivation significantly impacts consumers' impulsive buying behavior in e-commerce.